2021
DOI: 10.1101/2021.07.01.450707
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ad26.COV2.S elicited neutralizing activity against Delta and other SARS-CoV-2 variants of concern

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) continues to evolve and recently emerging variants with substitutions in the Spike protein have led to growing concerns over increased transmissibility and decreased vaccine coverage due to immune evasion. Here, sera from recipients of a single dose of our Ad26.COV2.S COVID-19 vaccine were tested for neutralizing activity against several SARS-CoV-2 variants of concern. All tested variants demonstrated susceptibility to Ad26.COV2.S-induced serum neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 7 publications
6
35
2
1
Order By: Relevance
“…The data reported here differ somewhat from those reported by Jongeneelen et al who found that Ad26.COV2.S-elicited antibody titers were mostly maintained against the variants 20 . In addition, Alter et al reported a 5-fold decrease in neutralizing antibody titer against Beta and 3.3-fold decrease against the Gamma variant by the sera from Ad26.COV2.S vaccination 21 which were less pronounced than those reported here.…”
Section: Discussioncontrasting
confidence: 99%
“…The data reported here differ somewhat from those reported by Jongeneelen et al who found that Ad26.COV2.S-elicited antibody titers were mostly maintained against the variants 20 . In addition, Alter et al reported a 5-fold decrease in neutralizing antibody titer against Beta and 3.3-fold decrease against the Gamma variant by the sera from Ad26.COV2.S vaccination 21 which were less pronounced than those reported here.…”
Section: Discussioncontrasting
confidence: 99%
“…The antibody titers remained stable for at least 71 days besides a 2.6-2.9-fold increase after the second-dose. Spike binding antibodies also variant [133]. In South Africa, D614G and 501Y.V2 strains of coronavirus demonstrated high levels of cross-reactivity in spike-binding assay (n=120) at least 29 days post-vaccination [134].…”
Section: Sinopharm (Inactivated Virus Vaccine)mentioning
confidence: 98%
“…However, these two studies support the notion that following completion of the second dose of vaccination, all the approved vaccines may induce cross-neutralization of at least some of the circulating SARS-CoV-2 variants. It has been showed that the single-shot Ad26.COV2.S is effective against the rapidly spreading Delta variant and other VOC (Jongeneelen et al, 2021). Although the VE of BNT162b2 and ChAdOx1 has been compared against Alpha and Delta variants showing similar efficacy (Stowe et al, 2021), there is no single study comparing the VE of all vaccines so far approved by the WHO against all VOC and VOI.…”
Section: Covid-19 Vaccines Against Sars-cov-2 Variantsmentioning
confidence: 99%